A novel multistage antigens ERA005f confer protection against Mycobacterium tuberculosis by driving Th-1 and Th-17 type T cell immune responses - Fan, Xueting; Zhao, Xiuqin; Wang, Ruibai; Li, Machao; Luan, Xiuli; Wang, Ruihuan; Wan, Kanglin; Liu, Haican (Frontiers in Immunology, 2023)
To date, tuberculosis (TB) also presents a major threat for human health in the world. In 2021, TB was the second cause of death after COVID-19 among infectious diseases. Bacillus Calmette-Gué rin vaccine (BCG), the only licensed TB vaccine, is ineffective to adult TB. It is urgent to develop new effective vaccines.In this study, we developed a novel multistage subunit vaccine (ERA005f) comprising various metabolic states-expressed protein antigens based on three immunodominant antigens (ESAT-6, Rv2628 and Ag85B). We utilized the E. coli prokaryotic expression system to express ERA005f and subsequently purified the protein through nickel affinity chromatography and anion exchange. The immunogenicity and protective efficacy of ERA005f and ERA005m were evaluated in Balb/c mice.Results: ERA005f was consistently expressed as an inclusion body in the prokaryotic expression system and a highly pure form of the protein was successfully obtained. Both ERA005f and ERA005m could significantly improve the IgG titer in serum. In addition, mice immunized ERA005f and ERA005m generated higher titers of antigen-specific IgG2a compared to other groups. Elispot results showed that compared with other groups, ERA005f increased the numbers of IFN-γ-secreting and IL-4-secreting T cells, especially the number of IFN-γ-secreting T cells. Meanwhile, ERA005f induced higher the number of IFN-γ + T lymphocytes than ERA005m. And beyond that, ERA005f This is a provisional file, not the final typeset article also improved the expression of cytokines, including IFN-γ, IL-12p70, TNF-α, IL-17 and GM-CSF and so on. Importantly, both ERA005f and ERA005m significantly inhibited the Mtb growth.The novel multistage antigens ERA005f elicited strong antigen-specific humoral response, Th-1 and Th-17 types' cell-mediated immunity in mice. Meanwhile, it can effectively inhibit H37Rv growth in vitro, and it represents a correlate of protection in vivo, indicating that the ERA005f may exhibit excellent protective efficacy against Mycobacterium tuberculosis H37Rv infection. Our study suggests that ERA005f has the potential to be a good multistage tuberculosis vaccine candidate.